2007
DOI: 10.1111/j.1447-0756.2007.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of multifetal pregnancies

Abstract: Assisted multifetal pregnancies were more likely to be delivered by cesarean section and had a higher rate of higher-order fetuses, preterm birth and neonatal prematurity-related complications with a longer hospital stay in both mothers and newborns, than spontaneous multifetal pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
3
2
Order By: Relevance
“…In this regard, our results are in contrast to those of other reports [1,10,13,25,29,33,34,36,42]. One study described a higher rate of elective surgical delivery [44], and three other studies report a higher rate of Caesarean section, in addition to prematurity and prematurity-related neonatal complications for ART twins [4,20,25]. In addition, the rate of Caesarean section observed in another German study differs markedly between ART (76.2 %) and SC (42.5 %) twins [16].…”
Section: Caesarean Sectioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In this regard, our results are in contrast to those of other reports [1,10,13,25,29,33,34,36,42]. One study described a higher rate of elective surgical delivery [44], and three other studies report a higher rate of Caesarean section, in addition to prematurity and prematurity-related neonatal complications for ART twins [4,20,25]. In addition, the rate of Caesarean section observed in another German study differs markedly between ART (76.2 %) and SC (42.5 %) twins [16].…”
Section: Caesarean Sectioncontrasting
confidence: 97%
“…We could not find any significant differences with regard to prematurity between our ART group (50 %) and our SC group (48.2 %). This is again in contrast to previous studies which described an increased frequency of prematurity in their ART twin collectives [4,8,10,13,17,20,21,25,27,29,33,34,36,38,41,45]. Reddy et al [31] reported that more than one half of all neonates are the products of multifetal gestations that are accompanied by an increase of prematurity complications.…”
Section: Prematuritycontrasting
confidence: 74%
“…3 Twin pregnancies are risk factors during pregnancy as they result in preterm deliveries and are frequently associated with medical complications like preeclampsia, gestational diabetes and antepartum haemorrhage. 2,4,5 Multiple pregnancies also result in poor perinatal outcome due to complications in babies like prematurity, low birth weight, growth restriction and congenital anomalies. Optimizing maternal, fetal and perinatal outcome is definitely a hurdle to be crossed in obstetrics, hence the need for further such studies.…”
Section: Introductionmentioning
confidence: 99%
“…The dangers of carrying and delivering multiple fetuses, including a higher risk for prematurity and low birth weight, are well documented (Koranantakul et al 2007).…”
Section: Welfare and Global Surrogacymentioning
confidence: 99%